Effect of Supplementing Conjugated Linoleic Acid Producing Bifidobacterial Strains on In vitro Rumen Fermentation Attributes - Jaglan, Neeru; Kumar, Sachin; Choudhury, Prasanta Kumar; Tyagi, Bhawna; Banakar, P. S.; Tyagi, Nitin; Tyagi, Amrish Kumar (Indian Journal of Animal Nutrition, 2020)
The present study was undertaken to evaluate the effects of supplementation of four conjugated linoleic acid (CLA) producing strains of Bifidobacteria isolated from rumen fluid samples of Murrah buffalo (Bubalus bubalis) on ruminal fermentation attributes based on a basal diet having roughage: concentrate in a ratio of 70:30. Results of the study showed that dosing Bifidobacterium strains (109 cells/ml) separately into in vitro incubation tubes neither affect the total gas nor methane (CH4) production after 24 h of incubation. Digestibility parameters showed no significant (P>0.05) changes with respect to in vitro dry matter digestibility (IVDMD), in vitro organic matter digestibility (IVOMD), or total ammonia-N content of fermentation fluid. However, volatile fatty acid (VFA) concentration was observed to be significantly increased (P<0.05) in the treatment samples with bacterial strains NB-191 and NB-184. While analyzing CLA content of incubation medium, a significant increase in the value was observed as compared to control tubes. Therefore, it can be concluded that the addition of potential CLA producing Bifidobacterial isolates to mixed rumen culture increased the CLA and VFA content without affecting digestibility and fermentation parameters.